2021
DOI: 10.1088/1755-1315/716/1/012106
|View full text |Cite
|
Sign up to set email alerts
|

Development of the sustainable human development index model in West Papua

Abstract: The West Papua Province has declared itself a sustainable development province by implementing various programs to achieve sustainable development goals (SDGs). The social, environmental, and economic factors in West Papua need to be linked to improving the HDI as one of the programs to achieve SDGs. The declining poverty rate in West Papua Province in 2010-2018 has had a significant impact on increasing the HDI of West Papua. This study aims to identify factors that affect the HDI and the dynamics and predict… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 10 publications
1
5
0
Order By: Relevance
“…The findings of this study are consistent with earlier work by Tjolli et al [37] which showed that HDI had an impact on lowering poverty. Al-Nuaimi and Al-Ghamdi [46] also showed that HDI supports economic development.…”
Section: The Effect Of the Human Development Index On Sustainable Dev...supporting
confidence: 93%
See 1 more Smart Citation
“…The findings of this study are consistent with earlier work by Tjolli et al [37] which showed that HDI had an impact on lowering poverty. Al-Nuaimi and Al-Ghamdi [46] also showed that HDI supports economic development.…”
Section: The Effect Of the Human Development Index On Sustainable Dev...supporting
confidence: 93%
“…In research conducted by Kroll et al [2], it was stated that HDI influences the development of SDGs. Meanwhile, in research from Quy [14] and Tjolli et al [37], HDI has a negative effect. Based on this statement, the following hypothesis is obtained:…”
Section: The Influence Of the Human Development Index On The Sdgsmentioning
confidence: 98%
“…Furthermore, the finding is an alternative to the means in increasing HDI based on fiscal capacity (Khusaini, 2020;Rizki & Saputra, 2018), political will (Amaluddin et al, 2018), and public services in the health sector (Candradewini & Nirmalasari, 2018). This study emphasizes the importance of the perspective on the methods of achieving development goals rather than the content of development such as human development (Lind, 2019;Scherbov & Gietel-Basten, 2020), infrastructure development (Castro, Taleires, & Silveira, 2021), sustainable environment (Jin et al, 2020;Lai & Chen, 2020;Lima et al, 2022;Tjolli et al, 2021), information and communication technology (N. H. Khan et al, 2019;Zhang & Danish, 2019), globalization (Asadi & Marin, 2019), economic development (Bhowmik, 2018;Kinnunen et al, 2019), and democracy (Gruczyn ska, 2018; Kinnunen et al, 2019).…”
Section: Resultsmentioning
confidence: 99%
“…More focused HDI studies within the Indonesian national scope have also been carried out by Hasanah, Bahri, & Fitriyani (2021) and Haseeb, Suryanto, Hartani, & Jermsittiparsert (2020). Meanwhile, studies in various regions in Indonesia have also been conducted by Ansyar, Padjung, & Salam (2021), Candradewini & Nirmalasari (2018), and Tjolli, Karuniasa, Rehiara, Jance, & Lestari (2021.…”
Section: Introductionmentioning
confidence: 99%
“…System dynamics is a problem analysis technique that imitates a complex, dynamic, nonlinear, and feedback-equipped system or abstraction form (Tjolli et al, 2021). A system dynamics model is capable of accepting system dynamics that require some interventions that need to be integrated throughout the simulation, increasing the model's complexity.…”
Section: Introductionmentioning
confidence: 99%